2003
DOI: 10.1007/s00425-003-1075-7
|View full text |Cite
|
Sign up to set email alerts
|

Slippery surfaces of carnivorous plants: composition of epicuticular wax crystals in Nepenthes alata Blanco pitchers

Abstract: Plants in the genus Nepenthes obtain a substantial nutrient supply by trapping insects in highly modified leaves. A broad zone of the inner surface of these pitchers is densely covered with wax crystals on which most insects lose their footing. This slippery wax surface, capturing prey and preventing its escape from the trap, plays a pivotal role in the carnivorous syndrome. To understand the mechanism of slipperiness, the present investigation aimed at an ultrastructural and physico-chemical characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 20 publications
7
92
0
2
Order By: Relevance
“…It has been reported that hydrophobic substrates reduced adhesion (Riedel et al 2003;Gorb et al 2004;Gorb and Gorb 2006a, b). However, we found here no significant correlation between the traction force of C. montrouzieri and contact angles of liquids on P. sativum leaflet surfaces.…”
Section: Wax-mediated Beetle Attachmentmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been reported that hydrophobic substrates reduced adhesion (Riedel et al 2003;Gorb et al 2004;Gorb and Gorb 2006a, b). However, we found here no significant correlation between the traction force of C. montrouzieri and contact angles of liquids on P. sativum leaflet surfaces.…”
Section: Wax-mediated Beetle Attachmentmentioning
confidence: 94%
“…Physicochemical properties of plant surfaces (wettability by water and the free surface energy) in terms of their influence on insect attachment have been recently discussed in some studies (Riedel et al 2003;Bohn and Federle 2004;Gorb et al 2004;Gorb and Gorb 2006a, b). It has been reported that hydrophobic substrates reduced adhesion (Riedel et al 2003;Gorb et al 2004;Gorb and Gorb 2006a, b).…”
Section: Wax-mediated Beetle Attachmentmentioning
confidence: 99%
“…waxes, trichomes) (Eigenbrode, 2004;Eigenbrode et al, 1996;Eigenbrode et al, 1999;Eigenbrode et al, 2000;Gorb and Gorb, 2002;Gorb and Gorb, 2006;Lee and Fearing, 2008;Raibeck et al, 2008). Plant waxes in particular are known to cause problems for foraging insects (Eigenbrode, 2004;Markstadter et al, 2000;Riedel et al, 2003). The differing frictional coefficients of the wax surfaces alter the ability of insect foot secretions to wet plant surfaces (Gorb and Gorb, 2006;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When visiting the pitchers, insects can fall into the traps, from which they are mostly unable to escape, and are digested by enzymes of the pitcher fluid and by the infauna inhabiting it. The numerous studies on the function of Nepenthes pitchers have focused on the mechanism of insect attraction (6,7), on the trapping of insects by alkaloid anesthesia (8), by slippery epicuticular wax crystals (3,5,9,10) or by downwardpointing lunate cells (3) of the inner pitcher wall, on the properties of the glandular zone (11), and on the nature of the digestive fluid (12)(13)(14). Only recently, L. Gaume et al (15) conducted the first comprehensive study on the trapping mechanism of Nepenthes by comparing the effect of the different pitcher surface zones and by separating the mechanisms of prey capture and retention.…”
mentioning
confidence: 99%
“…2, 5, 7). The waxy zone of Nepenthes pitchers is characterized by platelet-shaped aldehyde crystals protruding perpendicularly from the surface (9). These platelets not only detach and contaminate the surface of insect adhesive pads but also appear to interact with the insect's adhesive secretion to form an amorphous substance that impedes attachment (10).…”
mentioning
confidence: 99%